In vitro evaluation of aldoxime interactions with human acetylcholinesterase - Kovarik, Zrinka (Array, 2008)
Summary: We related the ability of eleven pyridinium and imidazolium aldoximes to reactivate tabun-inhibited human erythrocyte acetylcholinesterase with their molecular properties. Using molecular mechanics we performed conformational analysis to determine the flexibility of the aldoximes. Semi-empirical calculations show that differences in reactivation rates probably do not origin from different electron density on the oxygen of the oxime group, but can be explained by the steric hindrance within the aldoxime molecule. Tabun-inhibited acetylcholinesterase was efficiently reactivated by flexible bispyridinium para-aldoximes with propylene or butylene linker. Although pyridinium/imidazolium aldoximes with the oxime group in ortho-position did not show significant reactivation ability, they protected acetylcholinesterase against phosphorylation by tabun due to their high affinity for the native acetylcholinesterase. The aldoximes were examined for cytotoxicity on different cell lines and no cytotoxic effect was observed for doses of up to 400 µmol dm–3